EFEKTIFITAS PENYULUHAN KESEHATAN REPRODUKSI DAN SEKSUAL TERHADAP PENGETAHUAN CALON PENGANTIN DI KUA SAWAH BESAR PERIODE FEBRUARI-MARET 2020 - Eny Irawati (HSG (Health Science Growth) Journal, 2021)
Reproductive and sexual rights must ensure the safety and security of the bride-to-be, including obtaining complete information about reproductive and sexual health.The population in this study is brides-to-be in KUA Sawah Besar District, Central Jakarta with a total sample of 40 people taken with total sampling techniques.The method of data collection is done using questionnaires. From the results of the study obtained that the most age of respondents is the age of 20-25 years as many as 23 respondents (57.5%), the education of most respondents is high school that is 27 people (67.5%), the average knowledge of respondents about reproductive health before counseling is 66.35% and after counseling is 83.25%.Thus, it can be concluded that there is a difference in the value of knowledge before and after counseling with an increase in knowledge by 16.9% and there is an influence of counseling on the increase of respondents' annualization with a T test value of signification of P value of 0.000. Keywords: age, education, knowledge